Pemberdayaan Kader Posyandu dalam Mencegah Preeklampsia Melalui Olahan Edamame - Awatiful Azza; Danu Indra Wardhana; Tini Dwi Lestari; Tarissa Issa Septiana; Muhammad Andrian Maulana (Journal of Community Development, 2026)
Preeclampsia is a pregnancy complication that contributes to maternal morbidity and mortality, while the knowledge of posyandu cadres and pregnant women regarding preeclampsia prevention remains limited, particularly in the utilization of local nutritious food. The main problem faced by the community partners was the low level of understanding among cadres and pregnant women about preeclampsia and the suboptimal use of edamame as an alternative nutritional source for its prevention. This community service program aimed to empower posyandu cadres through health education and training in processing edamame into an easy-to-consume beverage for pregnant women. The methods applied included socialization, education on preeclampsia and the nutritional benefits of edamame, as well as demonstrations and hands-on training in preparing edamame latte. The activity involved 6 posyandu cadres, 2 midwives, 4 pregnant women, and 17 mothers with toddlers at Posyandu Dahlia 35, Glagahwero Village, Jember Regency. The results showed an increase in knowledge regarding preeclampsia prevention among participants by 95% and an improvement in skills related to edamame processing by 95%. This program had a positive impact on strengthening the role of posyandu cadres as community health educators and promoting the utilization of local food resources as a supportive strategy for preventing preeclampsia at the community level.